Design and development of gearing system for car simulator - Khairulanwar, Abd Rani (2010)
Nowadays, the prototype will be designed and be tested prior produces the real car. It is done to ensure better performance of the design especially for high cost products. The cost of prototype sometimes becomes higher and higher due to our demand to high performance system of the car itself. Therefore, it is important to have a system that can simulate the performance of the car before it can be used by the customer. For this purposes, the car simulators are being used as testing machine on car performance. This project will focus more on gearing system since that system is the most important parts for car performance. Simple electrical circuit will be design in order to take the data/signal on gearing design and to ensure the design is functional.